Current perspective on actinic keratosis: a review. (1st August 2017) - Siegel, J.A.; Korgavkar, K.; Weinstock, M.A.
Summary: Actinic keratoses (AKs) are common, with prevalence in the U.S.A. estimated at almost 40 million in 2004 and annual costs of > $1 billion (U.S.D.). However, there is no universally accepted definition of AK and thus it is difficult to identify reliably. AKs are lesions of epidermal keratinocytic dysplasia that result from chronic sun exposure and have the ability to progress to invasive squamous cell carcinoma (SCC), but clinicians disagree about whether AKs are premalignant lesions, superficial SCC in situ or epiphenomena of chronically sun‐damaged skin. Yearly AK to SCC progression rates of 0·6% were reported in an elderly population with multiple prior keratinocyte carcinomas (KCs); and rates of spontaneous AK regression have been reported to be > 50%, but regressed lesions often reappear. As AKs have both cosmetic consequences and potential for malignant transformation, there are multiple reasons for treatment. There is no current agreement on the most efficacious treatment, but 5‐fluorouracil has been shown to both prevent and treat AKs, and imiquimod and photodynamic therapy may have the best cosmetic outcomes. AKs may be treated to improve appearance and relieve symptoms, but the keratinocytic dysplasia that gives rise to malignancy, and sometimes appears as an AK, may be what actually threatens patient health. Thus, treatments should aim to decrease the risk of KC or facilitate KC diagnosis by reducing the potential for misidentification created when a KC appears in a field of AKs. Improved agreement among clinicians on AK definition may improve management.